2020
DOI: 10.1038/s41541-020-00227-x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant HA-based vaccine outperforms split and subunit vaccines in elicitation of influenza-specific CD4 T cells and CD4 T cell-dependent antibody responses in humans

Abstract: Although traditional egg-based inactivated influenza vaccines can protect against infection, there have been significant efforts to develop improved formats to overcome disadvantages of this platform. Here, we have assessed human CD4 T cell responses to a traditional egg-based influenza vaccine with recently available cell-derived vaccines and recombinant baculovirus-derived vaccines. Adults were administered either egg-derived Fluzone ® , mammalian cell-derived Flucelvax ® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…Previous studies reported that recombinant HA (rHA) expressed by the baculovirus/insect system shows good immunogenicity 14 16 . We next assessed the immunogenicity and protection of baculovirus-expressed H7 rHAs (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that recombinant HA (rHA) expressed by the baculovirus/insect system shows good immunogenicity 14 16 . We next assessed the immunogenicity and protection of baculovirus-expressed H7 rHAs (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mice immunized with adjuvanted SH/2 or HK/125 rHA had virus-specific antibodies in similar level and quality to those administered with adjuvanted GD/16 rHA at 500 ng/mouse and were protected from the lethal HPAI wt GD/16 challenge. In humans, Flublok® based on baculovirus-expressed rHA was reported to elicit superior antibody responses than inactivated egg- or cell-based influenza vaccines 16 . Human antibodies elicited by AH/1 rHA vaccination were reported to broadly cross-react with emerging H7 HAs 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Although subunit vaccines are generally considered to have limited capacity to boost cellular responses [ 23 ], recent studies have reported the induction of significant HA–specific CD4 T cell responses by Flucelvax [ 7 , 10 ]. While little is still known about the CD8 responses and their protein targets contained in this vaccine, here, we evaluated both CD4 and CD8 responses.…”
Section: Discussionmentioning
confidence: 99%
“…For the 2018–2019 influenza season, Flucelvax was designed to contain two influenza A (H1N1 Singapore/GP1908/2015 IVR-180 and H3N2 North Carolina/04/2016) and two influenza B virus strains (Iowa/06/2017 and Singapore/INFTT-16-0610/2016) [ 5 ]. Compared to conventional egg-based influenza vaccines, its production can be expanded to large-scale within a short timeframe without egg-specific adaptions and mutations [ 7 ]. Since licensure in 2016, studies have shown that Flucelvax is potentially superior to egg-based vaccines in preventing influenza infection both in terms of real-life effectiveness, as well as in the protective efficacy demonstrated during clinical trials [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, removal of these glycans, either through enzymatic means or through the use of alternative cell culture systems, to generate less-glycosylated HAs could afford enhanced breadth of protection. Studies investigating this hypothesis have demonstrated success in achieving wider protection and cross-reactivity by utilizing monoglycosylated and alternatively deglycosylated HA immunogens [ 34 , 35 , 36 , 37 ]. Specifically, treatment of embryonated chicken eggs with kifunensine, an inhibitor of α-mannosidase I-mediated glycosylation, in embryonated egg-based vaccine production, and virions with endoglycosidase H to trim their glycans to a monoglycosylated form, produced vaccines with superior HAI and neutralizing titers in mice [ 37 ].…”
Section: Alteration Of Glycosylation Sites In Ha Immunogensmentioning
confidence: 99%